Geostrategický význam Grónska - Uchytilová, Gabriela (Univerzita Karlova, Fakulta sociálních věd, 2022)
The diploma thesis entitled "Geostrategic Importance of Greenland" deals with the current geopolitical position of the island in the context of advancing climate change. This brings Greenland many opportunities, but also threats that could affect its further development. The main aim of the work is therefore to examine how the geographical location of the island in combination with the advancing climate change affects its development, especially towards the future full independence from the Kingdom of Denmark. The work maps the current situation of Greenland in terms of newly emerging opportunities as well as the threats it also faces. Furthermore, the work focuses on the relationship between Greenland and Denmark and tries to describe the strategic importance of the island for Denmark. Although the Arctic is an area where states have cooperated in the past decades, in recent years tensions have been growing in the region between the Russian Federation, which is increasing its military presence there, and Western states represented by the North Atlantic Alliance. In addition, China is trying to penetrate the region, which is not indifferent to the strategic importance of the region, and other non-Arctic actors, led by the European Union, are also turning their attention to the region. The. Diplomová práce nesoucí název "Geostrategický význam Grónska" se zabývá současným geopolitickým postavením ostrova v kontextu postupující klimatické změny. Ta přináší Grónsku mnoho příležitostí, ale i hrozeb, které by mohly ovlivnit jeho další vývoj. Hlavním cílem práce je tedy prozkoumat, jak geografická poloha ostrova v kombinaci s postupující klimatickou změnou ovlivňuje jeho vývoj, zejména směřování k budoucí úplné nezávislosti na Dánském království. Práce mapuje současnou situaci Grónska z hlediska nově se naskýtajících příležitostí i hrozeb, kterým čelí. Dále se práce zaměřuje na vztah Grónska a Dánska a pokouší se popsat, jaký strategický význam pro Dánsko ostrov má. Přestože je Arktida oblastí, kde v uplynulých ...